Autonomous Learning Material with Mind Mapping for EFL University Students: A Study of Extensive Reading (Conference on English Language Teaching, 2024)
The current educational paradigm has changed, shifting from teacher-centered to student-centered. Self-directed learning is now one of the most discussed topics. Therefore, a methode is needed to improve students autonomous learning. This study aims to explore the use of Mind Mapping media as a learning tool to teach broader reading skills, to improve memory, and note-taking skills. The present study used a qualitative case study approach based on self-directed learning. Data were collected through observation, semi-structured interviews with four EFL students consisting of two female and two male students at a university in Indonesian higher education getting involved in an extensive reading class. The results show that students' learning attitude is positively affected by autonomous learning with Mind Mapping. In other words, this method gives students the opportunity to experiment and take full responsibility for their own learning process. So that it can open the role of student creativity. Finally, The implication is discussed in this study.